Designing Ikhwan Shop Management System with Desktop-based Multi-User - Khakim, Lukmanul (Internet of Things and Artificial Intelligence Journal, 2024)
The Ikhwan Shop provides goods and cellphone repair services, but the system that runs in the shop records incoming and outgoing goods, and the results of repair services are still done by writing in a hand-written shop logbook. Therefore, a management system, an application designed to cover all activities running in the store, is needed. The activities are selling pulses, snacks, office stationery, receiving damaged cellphone repairs, and serving consignment of supplier goods. The system is equipped with a calculation of net and gross income and data collection related to employee salaries. After managers, cashiers, and technicians tested and implemented the system, it was concluded that it followed the business processes running at the Ikhwan shop. The system testing results with Blackbox show that all system functions can run well, so management activities run more effectively and efficiently.